Use of various MgO resources for high-purity Mg metal production through molten salt electrolysis and vacuum distillation - Hyeong-Jun Jeoung; Tae-Hyuk Lee; Youngjae Kim; Jin-Young Lee; Young Min Kim; Toru H. Okabe; Kyung-Woo Yi; Jungshin Kang (Journal of Magnesium and Alloys, 2023)
A green and effective electrolytic process was developed to produce high-purity Mg metal using primary and secondary resources containing MgO as a feedstock. The electrolysis of various MgO resources was conducted using a Cu cathode in MgF2 – LiF – KCl molten salt at 1043 K by applying an average current of 1.44 A for 12.5 h. The electrolysis of calcined North Korean magnesite and seawater MgO clinker yielded Mg alloys of MgCu2 and (Cu) phases with current efficiencies of 89.6–92.4%. The electrolysis of oxidized MgO-C refractory brick, aged ferronickel slag, and ferronickel slag yielded Mg alloys of MgCu2 and (Cu) phases with current efficiencies of 59.3–92.3%. The vacuum distillation of Mg alloys obtained was conducted at 1300 K for 10 h to produce high-purity Mg metal. After vacuum distillation, Mg metal with a purity of above 99.994% was obtained. Therefore, this study demonstrates the feasibility of the production of high-purity Mg metal from various MgO resources using a novel electrolytic process with a Cu cathode, followed by vacuum distillation.